2018
DOI: 10.1152/japplphysiol.00930.2017
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine increases both total work performed above critical power and peripheral fatigue during a 4-km cycling time trial

Abstract: The link between total work performed above critical power (CP) and peripheral muscle fatigue during self-paced exercise is unknown. We investigated the influence of caffeine on the total work done above CP during a 4-km cycling time trial (TT) and the subsequent consequence on the development of central and peripheral fatigue. Nine cyclists performed three constant-load exercise trials to determine CP and two 4-km TTs ~75 min after oral caffeine (5 mg/kg) or cellulose (placebo) ingestion. Neuromuscular functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 68 publications
10
60
1
3
Order By: Relevance
“…However, the change in EMGRMS was much larger than the change in CP. Although the mechanisms for this effect remain to be defined, this observation is in agreement, with Felippe et al (2018). Specifically, these authors reported that, compared to placebo, caffeine ingestion increased mean power output by ~4%…”
Section: Neuromuscular Functionsupporting
confidence: 82%
“…However, the change in EMGRMS was much larger than the change in CP. Although the mechanisms for this effect remain to be defined, this observation is in agreement, with Felippe et al (2018). Specifically, these authors reported that, compared to placebo, caffeine ingestion increased mean power output by ~4%…”
Section: Neuromuscular Functionsupporting
confidence: 82%
“…In the present study, caffeine ingestion (5 mg·kg −1 ) improved exercise performance by ∼2%, when compared to both placebo and acetaminophen. These findings are consistent with several other studies showing a positive effect of caffeine compared to placebo (2-2.4%) on performance in a 4-km cycling TT [26,38,39]. However, the comparison between the ergogenicity of caffeine and acetaminophen had not been investigated; therefore, our findings suggest that caffeine has a greater ergogenic potential than acetaminophen, at least during a high-intensity cycling TT as used in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…It is predictable therefore that caffeine ought to increase muscle recruitment. However, data from the literature are contradictory, with some studies showing an increased muscle recruitment with caffeine during a 4-km cycling TT [26] and lower reduction in voluntary activation of the vastus lateralis during intermittent isometric knee extension contractions [44], while others failed to find any effect of caffeine on motor unit recruitment [38,45,46]. These contradictory findings may be because caffeine can also influence spinal excitability and the muscle contractile apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…According to the funnel plots (Figs. 6 and 7) only one study [62] produced an estimate of effect size outside the calculated confidence intervals which suggests a low risk of publication bias across all studies.…”
Section: Resultsmentioning
confidence: 98%